2021
DOI: 10.1002/app.50543
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultraviolet aging on the structure, mechanical and gas permeability properties of hydrogenated nitrile butadiene rubber

Abstract: The effect of ultraviolet (UV) radiation on the structure and performance of hydrogenated nitrile butadiene rubber (HNBR) was studied in this paper. The HNBR was exposed to UV radiation for various durations (0, 7, 14, 21 and 28 days). The Fourier transform infrared spectroscopy (FTIR) results demonstrated that the surface molecular structures were oxidized to generate oxygenated species under UV radiation. The oxidative degree enhanced with the increase of aging time, resulting in thicker and denser cracks on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A broad peak at 3436 cm –1 in the CNF spectrum (Figure a) is attributed to the OH stretching resulting from the physical water adsorption. CH 2 asymmetric and symmetric stretching vibrations are represented by two low-intensity peaks at 2921 and 2854 cm –1 . Moreover, the peak at 1631 cm –1 is associated with the CC stretching, whereas the peak at 1384 cm –1 is related to the CN stretching …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A broad peak at 3436 cm –1 in the CNF spectrum (Figure a) is attributed to the OH stretching resulting from the physical water adsorption. CH 2 asymmetric and symmetric stretching vibrations are represented by two low-intensity peaks at 2921 and 2854 cm –1 . Moreover, the peak at 1631 cm –1 is associated with the CC stretching, whereas the peak at 1384 cm –1 is related to the CN stretching …”
Section: Resultsmentioning
confidence: 99%
“…CH 2 asymmetric and symmetric stretching vibrations are represented by two low-intensity peaks at 2921 and 2854 cm −1 . 34 Moreover, the peak at 1631 cm −1 is associated with the C�C stretching, 35 whereas the peak at 1384 cm −1 is related to the C�N stretching. 34 Figure 1b presents the characteristic peaks of DA, which comprise the primary amine (∼3338 cm −1 ), C�C stretching (∼1617 cm −1 ), and C�C bending (∼1501 cm −1 ).…”
Section: Characterization Of Cnfs 311 Fourier Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, if chain scission is the dominant reaction, a decrease in polymer chains interaction, and consequently, an increase in the mobility of molecular chains is observed, thus leading to a decrease in normalTnormalg . 36 However, for long aging times, crosslinking reaction usually dominates chain scission. This shows that the increase in normalTnormalg observed hinders the macromolecular dynamics and that a crosslinking reaction has occurred on the different NBR specimens 10,37 .…”
Section: Resultsmentioning
confidence: 99%
“…Cyclization reaction or reduction reaction may occur, affecting the service life of the rubber. [18][19][20][21][22] In the current published literatures, few studies have been reported on the aging mechanism for acrylonitrile content on HNBR, and few conclusions on the relevant aging mechanism were proposed.…”
Section: Introductionmentioning
confidence: 99%